2016
DOI: 10.1038/eye.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular muscle injury during endoscopic sinus surgery: an ophthalmologic perspective

Abstract: Purpose The purpose of this study is to describe the clinical characteristics and treatment results of medial rectus muscle (MR) transection incurred during endoscopic sinus surgery. Methods This retrospective study included 16 patients with MR transection incurred during endoscopic sinus surgery between 1994 and 2015. The operative notes of the surgical procedure, the pattern of strabismus, the type of muscle injury, the type of corrective strabismus surgery, and the surgical outcomes were reviewed. Results N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…This indicated that patients with congenital MRP often required strabismus surgery to correct their exotropia as performed by an ophthalmologist, whereas patients with MRP resulting from midbrain infarction are usually managed with drug therapy as administered by neurologists. Endoscopic sinus surgery and trauma (81.25%) were the most common causes of the lesions in our study, consistent with that of previously described 5‐14 . Extraocular muscle injury, especially of the medial rectus, is a rare complication of endoscopic sinus surgery.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This indicated that patients with congenital MRP often required strabismus surgery to correct their exotropia as performed by an ophthalmologist, whereas patients with MRP resulting from midbrain infarction are usually managed with drug therapy as administered by neurologists. Endoscopic sinus surgery and trauma (81.25%) were the most common causes of the lesions in our study, consistent with that of previously described 5‐14 . Extraocular muscle injury, especially of the medial rectus, is a rare complication of endoscopic sinus surgery.…”
Section: Discussionsupporting
confidence: 91%
“…The extremely rare incidence of isolated MRP has severely limited the availability of information on the aetiology, clinical findings, imaging features and therapeutic outcomes of this condition. Based on previous studies involving 59 cases, the most common causes for MRP included complications after endoscopic sinus surgery as observed in 38 (64.40%) patients, followed by trauma in 11 (18.64%), midbrain infarction in eight (13.56%), complications after strabismus surgery in one (1.70%) and medial rectus muscle disinsertion by scleral buckle in one (1.70%) patient 5‐14 . To our knowledge, it is the first time to review isolated MRP, not as a single case presentation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…MR is the most commonly lost muscle in strabismus surgery. MR loss has also been reported in other surgeries including retinal detachment repair, endoscopic lacrimal, or sinus procedures and orbital trauma repair 2, 3, 4. There is no intermuscular septum between the MR and the oblique muscles which makes the surgically lost MR difficult to retrieve 5…”
Section: Introductionmentioning
confidence: 97%